1993
DOI: 10.1083/jcb.122.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Calcium buffer injections delay cleavage in Xenopus laevis blastomeres

Abstract: Abstract. Microinjection of calcium buffers into the two-cell Xenopus laevis embryo delays cell division in a dose-dependent manner. Four calcium buffers in the BAPTA series with different affinities for calcium were used to distinguish between a localized calcium gradient regulating cleavage and the global calcium concentration regulating this event. DibromoBAPTA (Kd = 1.5 #M) was found to delay cleavage at the lowest intracellular concentration (1.3 mM) of the four buffers tested. The effectiveness of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…They also showed that the addition of 1 mM CaCl 2 has no effect on cyclin destruction (observation 10). Furthermore, the introduction of the calcium buffer BAPTA in dividing embryos slows but does not kill division cycles (8 Fig. 1 and are mathematically modeled in a manner similar to that used by Dupont and Goldbeter (23).…”
Section: Review Of Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also showed that the addition of 1 mM CaCl 2 has no effect on cyclin destruction (observation 10). Furthermore, the introduction of the calcium buffer BAPTA in dividing embryos slows but does not kill division cycles (8 Fig. 1 and are mathematically modeled in a manner similar to that used by Dupont and Goldbeter (23).…”
Section: Review Of Experimentsmentioning
confidence: 99%
“…One possibility is that these transients are essential, and that the mechanism that controls variations in [Ca 2ϩ ] i is a fundamental component of the master clock. The following observations (among others) suggest this scenario: (i) [Ca 2ϩ ] i transients* accompany early embryonic cell cycles (2-7); (ii) the injection of calcium buffers into intact Xenopus blastomeres delays or blocks division (8); and (iii) in the absence of division, [Ca 2ϩ ] i transients appear with the same frequency as that of division (3,5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This unambiguous role for Ca 2+ in cell-cycle progression at fertilization led to the discovery that Ca 2+ plays a role in cell-cycle progression in several different cell types. Evidence supporting a role for Ca 2+ in mitosis includes the fact that Ca 2+ transients have been recorded at key mitotic transitions including, nuclear-envelope breakdown (NEBD) (Poenie et al, 1985;Kao et al, 1990;Tombes et al, 1990), the metaphase-anaphase transition (Poenie et al, 1986;Ratan et al, 1988;Tombes and Borisy, 1989;Groigno and Whitaker, 1998) and cytokinesis (Fluck et al, 1991;Snow and Nuccitelli, 1993;Chang and Meng, 1995;Muto et al, 1996). These cell-cycle Ca 2+ transients are stimulated by cell-cycle-associated changes in the level of the Ca 2+ -mobilizing second messenger inositol-(1,4,5)-trisphosphate [Ins(1,4,5)P 3 ] (Ciapa et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that Ca 2+ binding proteins, such as synaptotagmin or calmodulin, function in the membrane fusion (Südhof and Rizo, 1996;Chamberlain et al, 1995). During cytokinesis, microinjections of calcium buffers result in inhibition of furrowing in Xenopus eggs (Miller et al, 1993;Snow and Nuccitelli, 1993). This may result from the inhibition of vesicle fusion as well as the inhibition of assembly and/or contraction of an actomyosin ring.…”
Section: Other Factorsmentioning
confidence: 99%